Researching tourism, leisure and hospitality for dissertations and theses - Mason, Peter, 1951- (Goodfellow Publishers, Limited, 2022)
Provides a step-by-step, user friendly guide to successfully researching and compiling your dissertation or thesis. Now in its second edition, this bestselling text has been fully revised and updated, and includes two new chapters looking at conducting mixed methods research, as well as analysing mixed methods research.